Odpowiedzi

2010-03-02T21:47:09+01:00
Korzystam ze wzoru na n-ty wyraz ciągu arytmetycznego
a(n) = a1 + (n-1) *r
a) (a6=20
(a10=4


a6 = a1 + (6-1)*r = 20
a10 = a1 + (10-1)*r = 4

a1 + 5r = 20
a1 + 9r = 4

a1 = 20 -5r
20 - 5r +9r = 4

a1 = 20 - 5r
4r = 4 -20

a1 = 20 - 5r
4r = -16

a1 = 20 -5r
r = (-16) :4

a1 = 20 - 5r
r = -4

a1 = 20 -5*(-4)=20 +20 = 40
r = -4

a1 = 40
r = -4
a(n) = a1 + (n-1) *r
a(n) = 40 + (n-1)*(-4)
a(n) = 40 - 4n +4
a(n) = 44 - 4n

d) (a3=4
(a5=2

a3 = a1 + (3-1)*r = 4
a5 = a1 + (5-1)*r = 2

a1 + 2r = 4
a1 + 4r = 2

a1 = 4 -2r
4 -2r + 4r = 2

a1 = 4 -2r
2r = 2 -4

a1 = 4 -2r
r = (-2): 2 = -1

a1 = 4 -2*(-1) = 4 +2 = 6
r = -1

a1 = 6
r = -1

a(n) = a1 + (n-1) *r
a(n) = 6 + ( n-1)*(-1)
a(n) = 6 -n +1
a(n) = 7 - n
3 1 3